2022
DOI: 10.1021/acs.jmedchem.2c01646
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Automated Synthesis of C(sp3)-Enriched Drug-like Molecules via Negishi Coupling and Novel, Automated Liquid–Liquid Extraction

Abstract: Herein, we report an end-to-end process including synthesis, work-up, purification, and post-purification with minimal human intervention using Negishi coupling as a key transformation to increase Fsp3 in bioactive molecules. The main advantages of this protocol are twofold. First, the automated sequential generation of organozinc reagents from readily available alkyl halides offers a large diversity of alkyl groups to functionalize (hetero)­aryl halide scaffolds via Pd-catalyzed Negishi coupling in continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
(59 reference statements)
2
15
0
Order By: Relevance
“…Results showed that all combinations produced the desired compounds in reasonable yield except when the organozinc derived from azetidine C was used where product was not detected, probably because of its lower nucleophilicity. Compounds 32A , 33A , 34A , 33B , 35B , 36B , 31D , 32D , 33D , and 35D were successfully purified by automated mass-triggered preparative HPLC in suitable amounts for biological evaluation . Taken as a whole, this study clearly supports the automated flow approach for library synthesis.…”
supporting
confidence: 58%
“…Results showed that all combinations produced the desired compounds in reasonable yield except when the organozinc derived from azetidine C was used where product was not detected, probably because of its lower nucleophilicity. Compounds 32A , 33A , 34A , 33B , 35B , 36B , 31D , 32D , 33D , and 35D were successfully purified by automated mass-triggered preparative HPLC in suitable amounts for biological evaluation . Taken as a whole, this study clearly supports the automated flow approach for library synthesis.…”
supporting
confidence: 58%
“…Advances in automated liquid–liquid extractions, , including microdroplets, and solid phase extraction (SPE)/​resin cleanup methods offer potentially faster and cheaper alternativesbut they cannot match the generic capabilities of C18 HPLC, with a wide compound structure range and high purity levels. Sample preparation, using SPE, for crude samples and advanced techniques of “trap and release” of “heart-cut” samples, combined with LCMS, offer the ultimate purification solution.…”
Section: Scalementioning
confidence: 99%
“…In recent years, progress has been made in developing low-cost HTS platforms [23] for the synthesis, purification and analysis of compounds. [24][25][26][27] We previously completed a fragment screen against the second bromodomain of the pleckstrin homology domain-interacting protein (PHIP(2)), a multidomain protein involved in various cellular processes including cellular growth and mobility [18] that has been implicated in a number of aggressive cancers including BRAFnegative melanomas, breast and lung cancer. [28,29] Following up on the piperazine hit, F709, from this screen, we implemented a growth array synthesis exercise using a low-cost OpenTrons OT-1 TM robotics-based synthesis platform, which allows for a quick survey of the chemical space around a fragment hit.…”
Section: Introductionmentioning
confidence: 99%